MAICC model: development of complex thinking through citizen science project evaluation - Olivo-Montaño, Pamela Geraldine; Sanabria-Z, Jorge; Molina-Espinosa, José Martín; Quintero-Gámez, Lorena; Velarde-Camaqui, Davis; Sánchez-Salgado, Lisset Abril; Gonzalez-Mendoza, Miguel; Breda, Adriana; Morales-Maure, Luisa; Alvarez-Icaza, Inés (Frontiers in Education, 2024)
As traditional education systems struggle to keep up with technological advances, incorporating open science into Education 5.0 is critical to addressing student skills gaps. In this study, the MAICC model is introduced, a tool designed to foster complex thinking in higher education students through the evaluation of citizen science projects. It integrates research-based learning and service learning, and helps develop critical and reflective skills by applying them to real-life settings. To assess student engagement and skills development, a mixed methods approach combining qualitative and quantitative analysis was used. Findings indicate that the MAICC model promotes complex thinking, enhances critical thinking through citizen science project evaluation, and features an emphasis on citizen science and educational technology. Discussion highlights citizen science’s important role in education and suggests future research exploring its wider application across disciplines and contexts to enhance 21st century skills.